A baseline study of issues and challenges playing out on teachers in the implementation of the new grade 3 science and technology curriculum at four primary schools in Chitungwiza district - Tsveture, Caroline (Midlands State University, 2019)
This study sought to investigate the issues and challenges playing out on teachers in the implementation of the new grade 3 science and technology curriculum. Further, the study sought to establish the nature of the challenges and how they can be overcome. In order to better illustrate a more detailed picture of the challenges playing out on teachers in implementing the new curriculum, a mixed method research design was implemented where data was collected using both qualitative and quantitative design. A survey was conducted, where twenty teachers from four schools purposefully selected were asked to fill in a questionnaire whilst interviews were conducted with six teachers. From this study, it was found that grade three teachers are facing challenges in the implementation of the new curriculum. These challenges include insufficient learning resources, absence of science laboratories, lack of ICT gadgets, overcrowded classrooms and lack of in service training. Lack of enough funding by the government was one major contributing factor. The teachers indicated that they were failing to cope with the demands of implementing the new curriculum due to these challenges. There was a resolution that Government should ensure that there is adequate funding for the implementation of the new curriculum to achieve the desired goals. Furthermore, there is need for training of teachers to support curriculum implementation.